Front Cover: 2D Linear Trap Array for Quantum Information Processing (Adv. Quantum Technol. 11/2020). Issue 11 (6th November 2020) - Holz, Philip C.; Auchter, Silke; Stocker, Gerald; Valentini, Marco; Lakhmanskiy, Kirill; Rössler, Clemens; Stampfer, Paul; Sgouridis, Sokratis; Aschauer, Elmar; Colombe, Yves; Blatt, Rainer
Abstract : The major challenge for trapped‐ion quantum computers is to scale‐up the number of qubits while preserving a high degree of control over the quantum states. The cover illustrates a scalable quantum processor with a two‐dimensional lattice of ion qubits confined by an array of linear surface traps. Entanglement of nearest‐neighbor ions is mediated by a Coulomb interaction with tunable strength. A configurable lattice connectivity extends the options for emulating 2D spin systems. Further information on the design, fabrication and commissioning of a prototype processor, as well as strategies to scale‐up the device, are given in article number 2000031 by Philip C. Holz and co‐workers.